Analysis of the internal environment of service infrastructure organization in the context of the expansion of Industry 4.0 technologies - V.G. Zharov (Векторы благополучия: экономика и социум)
The paper analyzes the internal environment of service infrastructure enterprises in order to identify and specify aspects that hinder the development of economic relations in the context of an active growth of the range of digital services. The paper considers the composition and functions of the components and (or) groups of components included in the internal environment. With their help the service infrastructure enterprise carries out its business activities and interacts with the external environment. The most significant of them have been identified for the current conditions. The importance of the research topic is due to the need to identify weaknesses in the components of the internal environment of service infrastructure enterprises and to search for priority areas for its adaptation to economic relations emerging in the context of the expansion of Industry 4.0 technologies. Methods. Methods of analysis, synthesis, induction, deduction, comparison, generalization and logic, system‐structural and problem‐oriented approaches, infographic modeling method, which was used for graphical interpretation of the system of connections of components of the internal environment of the organization of the service infrastructure. The information base of the research was publications in reputable media devoted to the consideration of theoretical and practical aspects of the functioning of the organization internal environment, analytical materials of periodicals and online publications, statistical data on the problems studied in the article. Results. The conducted research made it possible to identify the key components, weaknesses in the structure of the internal environment of the organization of service infrastructure and identify their weaknesses. Problems were found in the field of training qualified personnel, organizational structure and financial block. The study showed that in the context of the expansion of Industry 4.0 technologies, the personnel component of the internal environment of the organization of service infrastructure plays the key role.